Distress, Appraisal, and Coping Among the Frontline Healthcare Provider Redeployed to the Epicenter in China During COVID-19 Pandemic - Ji, Zhongliang; Han, Wei; Deng, Zhe; Lu, Kailin (Frontiers in Psychology, 2021)
Abstract: Objective, The central issue of this research is to evaluate the extent of cognitive appraisal and coping processes within the pandemic encounter and determines their influence on HPDE (frontline healthcare providers who had been dispatched to the COVID-19 epicenter)distress symptoms Materials and methods An electronic survey of the HPDE and HPOF (frontline healthcare providers who worked in their original medical facility ) was conducted from March 1 to 15, 2020. Two variables- appraisal (measured with an 18-item questionnaire) and coping (measured The Brief Cope questionnaire) were used in the analysis in order to explain distress symptoms(Impact of Event Scale-Revised) Results A total of 723 eligible respondents completed the survey with a response rate of 57.3% (351 HPDE and 372 HPOF). The mean IES-R scores of HPDE respondents were 26.47±11.7. Of HPDE respondents 246 (70.09%) reported distress symptoms(score 9-88). The scores of intrusion, avoidance, and hyperarousal for HPDE were 10.28±4,7,8.97±4.3, and7.20±3.2 respectively. The respondents had higher scores in overall distress and three subscales than HPOF. Appraisal and coping variables explained 77% of the distress variance. Five appraisal variables (health of self, health of family/others, virus spread, Vulnerability or loss of control, and general health) were positively associated with distress symptoms. Four coping variables (active coping, positive reframing, self-distraction, and behavioral disengagement were negatively associated with distress level, whereas self-blame was positively associated with distress symptoms. Regarding the appraisal, HPDE's scores were significantly higher than HPOF's (all P values < 0.05); Whereas being isolated was not significantly different between HDPE nurses and HPOF nurses. HPDE was significantly more likely to use humor, emotional support, instrumental support, self distractions, venting, substance use, denial, behavioral disengagement, and self-blame (P < 0.05). Whereas HPOF was significantly more likely to active coping, acceptance. (P< 0.05). HPDE doctors were significantly more likely than nurses to use active coping and acceptance (P< 0.05), whereas HPDE nurses were significantly more likely to use emotional support and use self-blame (P< 0.05) Conclusion HPDE respondents had a higher distress level. We should provide proactive psychological support based on specific appraisal and coping variables